The Urge to Purge: Forecasting Erdogan's Political Survival Following the Failed Coup. Issue 4 (November 2018) - Easton, Malcolm R.; Siverson, Randolph M.
Drawing upon earlier research on the post failed coup survival of political leaders, we offer an ex ante in sample estimate of the likely political survival of Turkish President Recep Tayyip Erdogan following the fail coup of 2016. Depending on the assumption made about when he entered office, we conclude that his tenure is likely to endure until 2026, a result that was reached before his recent call for a snap election and its implications. We conclude with a brief discussion of the policy implications of President Erdogan's likely length of tenure.